Advancing Transformative Eco-social Change: Shifting from Modernist to Holistic Foundations. Issue 2 (3rd April 2019) - Boetto, Heather
ABSTRACT: This paper proposes a reconciliatory, integrative, and transformative way forward for addressing philosophical incongruities between the emerging foundations of eco-social work and inherent modernist assumptions underpinning conventional social work practice. Although modernity has enabled the profession to pursue certain freedoms, such as individual empowerment and self-determination, a modernist worldview is today critiqued for philosophical assumptions associated with the unsustainable use of Earth's natural resources. By advancing transformative eco-social change, opportunities to broaden the profession's conventional philosophical base to include holism and interdependence with the natural world will be explored. Implications centre on the need to incorporate perspective transformation and critical reflexivity, and to revise the framing of fundamental documents, such as codes of ethics, practice standards, and education requirements. By integrating transformative eco-social change, social work can improve the capacity to develop a coherent and ethical response to ecological and social problems. IMPLICATIONS: Philosophical incongruities between inherent modernist assumptions underpinning conventional social work practice and the emerging foundations of eco-social work represent a major dilemma for the profession. Transformative eco-social change, involving the integration of philosophical principles emphasising holism and interdependence with the natural world is critical for developing a coherent and ethical approach to addressing ecological and social problems. Transformative change to broaden social work's conventional philosophical base in education and practice contexts can include the integration of perspective transformation, critical reflexivity, and the revision of professional policy documents.